IMPLEMENTASI METODE PEMBELAJARAN FASTER IS BETTER BERBASIS PEER TEACHING SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 9 YOGYAKARTA - Pranesti, Arin; Hidayah, Nurul; Latri, Sekar (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract This study aims to increase the learning motivation through the implementation of peer teaching-based faster is better learning method in State Senior High School 9 Yogyakarta. The method used in this study is classroom action research developed by Kemmis and Taggart. The subjects of this study are 21 students of grade XI of Social Science of SMAN 9 in Yogyakarta. The object of this study, learning motivation, is expected to increase through the implementation of the peer teaching learning method. The data were collected by using questionnaires and field notes. The results show that in the first cycle of the research,the motivation of most students was (64.99%). Based on the observations, in the second cycle the students' motivation has increased by 1.19% to reach 66.18% in the second cycle.